2017
DOI: 10.1515/msp-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing temperature on the structural and optical properties of As30Te70 thin films

Abstract: Chalcogenide glasses have attracted much attention largely due to their interesting physical and chemical properties. Though few published articles exist on the As-Te system, little is known about the optical properties of eutectic or near eutectic composition of As-Te system upon heat treatment. Therefore, this paper reports the effects of annealing temperature on the structural and optical parameters of As 30 Te 70 thin films. The bulk and thin films of 150 nm thick As 30 Te 70 chalcogenide glasses were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…1 reveal that the bulk As 30 Te 60 Ga 10 glass exhibits an endothermic glass transition, one distinct exothermic crystallization reaction, and endothermic melting peaks at 402.98 K, 495.22 K, 515.98 K, and 638.09 K, respectively. The observed glass transition temperature of the studied glass is higher than that of As 30 Te 70 composition, which can be attributed to the increased connectivity due to the addition of Ga [6]. This observation agrees with other ternary systems, such as As-Te-In and As-Te-Al [12,34].…”
Section: Structural Analysissupporting
confidence: 86%
“…1 reveal that the bulk As 30 Te 60 Ga 10 glass exhibits an endothermic glass transition, one distinct exothermic crystallization reaction, and endothermic melting peaks at 402.98 K, 495.22 K, 515.98 K, and 638.09 K, respectively. The observed glass transition temperature of the studied glass is higher than that of As 30 Te 70 composition, which can be attributed to the increased connectivity due to the addition of Ga [6]. This observation agrees with other ternary systems, such as As-Te-In and As-Te-Al [12,34].…”
Section: Structural Analysissupporting
confidence: 86%
“…The observed melting point, 622 ± 0.5 K, is in agreement with the melting point of As 2 Te 3 phase reported elsewhere [9]. Also, the existence of Ga shifts other characteristic temperatures by about 5 K compared to the As 30 Te 70 system [12]. The values of T g , T c1 , T c2 , T p1 , and T p2 increased with the heating rate.…”
Section: Structural Characterizationsupporting
confidence: 90%
“…According to Table 1, while average crystallite size increased with annealing temperature, the dislocation density and strain decreased accordingly. This observation indicates improved crystallinity due to the heat treatment which agrees with studies reported on some other chalcogenide thin films [11][12][13]. Figure 3a shows the DSC curves of As 30 Te 67 Ga 3 glass at different heating rates (from 5 to 25 K/min).…”
Section: Structural Characterizationsupporting
confidence: 89%
See 1 more Smart Citation
“…The low‐temperature phase (formed during the first crystallization peak) could not be identified by XRD, whereas the high‐temperature phase (analyzed after the second crystallization peak) was a mixture of low‐temperature phase and C2/m As 2 Te 3 —indicating phase separation and recrystallization into a more stable monoclinic phase. Regarding the present data, it is worth reminding that the fully crystalline samples exhibited monoclinic structure but showed no presence of identifiable phase‐separated phases (As 2 Te 3 , As, Se, or Te), which by the way rules out one of the alternative theories attributing the second crystallization peak to precipitation of phase‐separated Te. The most probable explanation is therefore that the first crystallization peak in the Te‐rich (As 2 Se 3 ) 100− x (As 2 Te 3 ) x glasses (see Figure ) is initiated by formation of the cubic AsSe(Te) phase that immediately partially recrystallizes into a monoclinic As 2 Se(Te) 3 .…”
Section: Resultsmentioning
confidence: 44%